Numerical Feedback Roundness Affects the Choice of the Self vs. Others as a Reference Point - Meyrav Shoham; Nira Munichor (Frontiers in Psychology, 2021)
People can use social or personal information as a reference point against which they compare their performance. While previous research has shown that reference point choice can be affected by individual characteristics, situational factors, and goals, we suggest that properties of the performance feedback itself can also play a role in this choice. We focus on the effects of round vs. precise numerical feedback on reference point preferences. In three studies, we show that people are more likely to use themselves as a reference point to evaluate their performance following a feedback in the form of a round score (e.g., a score of 70 in a task) and to use others as a reference point following a precise score (e.g., a score of 71). Study 1 shows decreased interest in comparisons with others following round rather than precise feedback. Study 2 shows that round (vs. precise) feedback also increases actual choice of the self (vs. others) as a reference point. Study 3 demonstrates that the effect of the numerical feedback on reference point preferences extends to the choice of a benchmark for future comparisons. We discuss the implications of our results for the literature and practice, including how this can be used to encourage desirable behaviors.